2012
DOI: 10.1093/ejo/cjs051
|View full text |Cite
|
Sign up to set email alerts
|

Interceptive orthodontic treatment in bullied adolescents and its impact on self-esteem and oral-health-related quality of life

Abstract: The aim of this follow-up study was to measure the self-reported frequency and severity of bullying in orthodontic patients previously identified as being bullied, who have commenced interceptive orthodontic treatment, and to investigate the effect on an individual's self-esteem and oral-health-related quality of life (OHRQoL). Forty-three adolescents previously identified as being bullied due to the presence of a malocclusion were invited to take part in a follow-up study following commencement of orthodontic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 27 publications
4
92
2
11
Order By: Relevance
“…[51][52][53][54][55][56][57] Victims are particularly concerned when they are teased about the appearance of their teeth 51 and orthodontic treatment can help to alleviate this. 58 Research is now focussed on ways of measuring the physical, functional, emotional and social impacts of conditions s daily life through the various concepts of quality of life, health and oral health-related quality of life.…”
Section: Social Well-beingmentioning
confidence: 99%
“…[51][52][53][54][55][56][57] Victims are particularly concerned when they are teased about the appearance of their teeth 51 and orthodontic treatment can help to alleviate this. 58 Research is now focussed on ways of measuring the physical, functional, emotional and social impacts of conditions s daily life through the various concepts of quality of life, health and oral health-related quality of life.…”
Section: Social Well-beingmentioning
confidence: 99%
“…Al final de los 48 meses de tratamiento se observó que el grupo que recibió ortodoncia interceptiva experimentó 33,0% de mejora en PAR y el 46,9% en ICON, mientras que el grupo que recibe ortodoncia integral tiene un 59,2% de PAR y el 60,9% para ICON. Seehra et al,(2012) en su artículo hace referencia a la influencia psicosocial del tratamiento de ortodoncia interceptiva en adolescentes de Inglaterra. La muestra estuvo compuesta por 27 pacientes que presentaran a lo menos 2 episodios de intimidación al mes producto de su maloclusión.…”
Section: Resultsunclassified
“…Unesthetic occlusal traits may induce unfavorable social responses among adolescents, such as nicknames and teasing by schoolmates 19 . Others have found that the presence of some occlusal traits is a significant indicator of self-reported bullying among adolescents 20 . Future studies should be conducted to investigate whether orthodontic treatment in preschool children with malocclusion can improve OHRQoL.…”
Section: Discussionmentioning
confidence: 98%